EVALUASI KINERJA PARKIR DI RUMAH SAKIT OTAK DR. DRS. M. HATTA BUKITTINGGI - Chairani, Melisa; Ishak, Ishak; Dewi, Selpa (Jurnal Riset Multidisiplin Agrisosco, 2023)
Bukitinggi Brain Hospital is one of the best standardized and superior hospitals in Bukittinggi. From year to year, public visits to the Brain Hospital are increasing, so that many vehicles are parked at the hospital and need a proper parking space in the Bukittinggi Brain Hospital area. The method used is by conducting a preliminary survey at the study site, collecting primary data and secondary data and then analyzing the data obtained. From the results of the study, it was found that the space requirement was 68 for cars and 113 for motorbikes, while the comparison of the actual parking space requirements with the standard parking space requirements applicable at the Bukittinggi Brain Hospital was 2.23 beds/SRP and 1.37 beds/SRP for Standard Director General of Transportation 1996. It can be concluded that the parking area for motorbikes is still safe and does not experience a shortage of SRP (Parking Space Unit) while for car parking there is a shortage of parking space of 28 SRP (Parking Space Unit) with a size for one car of 2.3 x 5 meters, so the area of land that needs to be added is (2,3 x 5 x 170 x 117) = 228,735 m^2 for car parking.